A study of hepatobiliary involvement in adult patients with sickle cell disease - Mohanty, Ambika Prasad; Yellapu, Venkatesh; Kumar, Kanduri Manoj; Saxena, Akshay; Deo, Dandi Suryanarayana (International Journal of Advances in Medicine, 2020)
Background: Sickle cell disease (SCD) encompasses a group of hemoglobinopathies characterized by a single amino acid substitution in the ß-globin chain. Hepatobiliary complications are frequent among sickle cell disease patients. Sickle cell disease has been extensively studied. However, data about hepatobiliary abnormalities among the adult age group are limited. Aim of our study aims to find the prevalence of hepatic-biliary involvement in Sickle cell disease in adult patients admitted to our hospital. Methods: A prospective study was done for a period of two years from October 2017 to October 2019. Subjects of both sexes above the age of 18 years with SCD admitted to our hospital were enrolled. Thorough history taking, full clinical examination, hematological and biochemical parameters assessment, and abdominal ultrasonographic studies were performed to all patients. Results: The results obtained showed that 59% of patients had hepatobiliary involvement. The most common symptom among these patients was bone pain, and the pallor was the most common sign. Biochemical tests revealed reduced hemoglobin concentration, elevated bilirubin, and compromised liver function. The most common ultrasound finding in this study was hepatomegaly, hepatosplenomegaly, cholelithiasis, and gall bladder sludge. The incidence of viral hepatitis was low compared to previous studies. Other hepatobiliary complications were cholelithiasis (14%), benign hyperbilirubinemia (14%), cholecystitis (8%) hepatic crisis (9%), hepatic sequestration (1%) , liver cirrhosis (1%), choledocholithiasis (1%) and cholangitis (1%). Conclusions:Hepatobiliary complications, particularly gallbladder diseases, are frequent among SCD patients. The early detection of hepatobiliary complications by repeated ultrasound screening and liver function tests is significant as their frequency and intensity are related to the patient’s age and the duration.